Integrative Analysis of Epidemiological Profile of Sensitization Clinical Laboratory Markers in Children: Cross-Sectional Study Results - L. G. Levina; L. S. Namazova-Baranova; E. A. Vishneva; K. S. Volkov; K. Y. Efendieva; A. A. Alekseeva; V. G. Kalugina; P. S. Arimova (Педиатрическая фармакология)
Background. The prevalence of various allergic diseases has increased worldwide in recent decades. Allergy diagnosis in children should be economically optimal and as sparing as possible, while ensuring the high quality of medical care. Objective. The aim of the study is to develop optimal algorithms for analysis of sensitization profile in children with allergy family history, or suspected allergy, or atopy phenotype. Methods. Complete examination of 153 children aged from 1 to 17 years 11 months was performed. Children were divided in 4 groups according to the presence and characteristics of complaints, the presence of allergic disease. Sensitization was determined via the “gold standard” of allergy diagnosis — the ImmunoCap method (Phadia, Sweden), and the results of skin testing. Results. 97 (63.4%) children have shown sensitization to various allergens. We have revealed seasonal manifestation of allergy in children to various allergens: Fagales in 89-92% of cases, grasses in 68-72% of cases, weeds in 39-57% of cases. Complaints of all-year manifestations of allergic rhinitis were revealed in 24% of cases to cat dandruff, complaints of coughing and/or bronchospasm — in 100% of cases to birch pollen and in 35% of cases to house dust. The sensitization analysis has revealed strong correlations with confirmed statistical significance between pollen allergen sensitization classes in groups of different plants. Conclusion. Optimal algorithms for sensitization diagnosis in children living in Moscow agglomeration were developed according to the obtained results and revealed correlations.